Dry eye disease in patients with type II diabetes mellitus: A retrospective, population-based cohort study in Taiwan - Pan, Li-Yen; Kuo, Yu-Kai; Chen, Tien-Hsing; Sun, Chi-Chin (Frontiers in Medicine, 2022)
Purpose To investigate the risk and protective factors of dry eye disease (DED) in patients with type II diabetes mellitus (DM). Design A retrospective cohort study using Chang- Gung research database collecting data from 2005 to 2020. Methods Patients with type II DM were included, and those with previous ocular diseases were excluded. Ten thousand twenty nine developed DED (DED group), and 142,491 didn't (non-DED group). The possible risk and protective factors were compared and analyzed using the logistic regression model. Results A majority of the DED group were female with significantly higher initial and average glycated hemoglobin levels, and higher incidence of diabetic neuropathy and retinopathy. In conditional logistic regression model, advanced age was a risk factor. After adjusting for sex, age, and DM duration; average glycated hemoglobin level, diabetic neuropathy, retinopathy, and nephropathy with eGFR 30 ~ 59 and intravitreal injection, vitrectomy, pan-retinal photocoagulation, and cataract surgery were contributing factors of DED. Considering antihyperglycemic agents, DPP4 inhibitor, SGLT2 inhibitor, GLP-1 agonist, and insulin monotherapy and dual medications combining any two of the aforementioned agents were protective factors against DED compared with metformin alone. In the monotherapy group, SLGT2 inhibitor had the lowest odds ratio, followed by GLP1 agonist, DPP4 inhibitor, and insulin. Conclusions DED in patients with DM is associated with female sex, advanced age, poor diabetic control, microvascular complications and receiving ocular procedures. GLP-1 agonist, SGLT-2 inhibitor, DPP4 inhibitor, and insulin are superior to metformin alone in preventing DM-related DED. A prospective randomized control trial is warranted to clarify our results.